2021
DOI: 10.3390/rs13152960
|View full text |Cite
|
Sign up to set email alerts
|

GPS-Based Multi-Temporal Variation in Precipitable Water over the Territory of Poland

Abstract: An increase in temperature causes higher evaporation of water from water bodies; consequently, the water content in the atmosphere also increases. The precipitable water (PW), as the water content in the atmospheric air column, is therefore an important parameter to consider when studying climate change. The aim of this study was to analyse multi-annual precipitable water data derived from a dense Global Navigational Satellite Systems (GNSS) network. Twelve years of observations from over a hundred ASG-EUPOS s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…This is due to the limited number of in situ stations with traditionally long periods of data records for meaningful exploration of PW, unlike other regions in the mid-latitude of the Northern Hemisphere. Preliminary results of the spatial variability of PW over Poland on the basis of GNSS data were presented in 2021 [61], supported with a geostatistical modeling approach for spatial interpolation. In our work, we have used high temporal and spatial resolution meteorological data, provided by the WRF model, to present the long-term gridded climatology of PW over Poland.…”
Section: Introductionmentioning
confidence: 87%
“…This is due to the limited number of in situ stations with traditionally long periods of data records for meaningful exploration of PW, unlike other regions in the mid-latitude of the Northern Hemisphere. Preliminary results of the spatial variability of PW over Poland on the basis of GNSS data were presented in 2021 [61], supported with a geostatistical modeling approach for spatial interpolation. In our work, we have used high temporal and spatial resolution meteorological data, provided by the WRF model, to present the long-term gridded climatology of PW over Poland.…”
Section: Introductionmentioning
confidence: 87%
“…Studies of central and eastern Europe, based on precipitable water (PW) extracted from GNSS data, have shown that, in recent years, the magnitude of this parameter varies from year to year and from season to season. The results of the studies show differences in the magnitude of precipitation water directly related to geographical location and seasonal variations and trends [26]. Due to ongoing climate change on a global as well as local scale, a further increase in PW values over the CEE region directly linked to a systematic increase in temperature is expected.…”
Section: Introductionmentioning
confidence: 91%
“…Influences of the Atlantic Ocean and the Eurasian continent clash over Europe, which means that the western part of Europe is predominantly influenced by the Atlantic, while the eastern part is mainly influenced by the continent's interior (Eurasia). Central and eastern Europe are located in the zone that mixes both influences (the climate varieties are maritime and continental) [26]; hence, the atmospheric conditions prevailing in this part of the continent are extremely complicated and difficult to forecast. The contribution of air masses from the Arctic and Atlantic oceans to meteorological and, in the longer term, climatic conditions is significant, as described in [27,28].…”
Section: Introductionmentioning
confidence: 99%